Acyclovir as a Potential Add-on Therapy in COVID-19 Treatment Regimens - Fatemeh Heidary; Sedigheh Madani; Reza Gharebaghi; Fahimeh Asadi-amoli (Tabriz University of Medical Sciences, 2021)
Background: There are successful reports of the concomitant management of herpes infection and coronavirus disease 2019 (COVID-19), using both acyclovir (ACV) and COVID-19 treatment regimens. Furthermore, ACV has been proposed to effectively treat COVID-19, through various mechanisms, such as inhibition of viral proteases, multiple viral gene expressions, and RNA dependent RNA polymerase (RdRP). Therefore, this study aimed to review the reported cases of patients with concomitant herpes infection and COVID-19, receiving concurrent antiviral drugs for herpetic lesions. Methods: A search was done to find the relevant articles, published between December 2019 and December 2020, with no language limitations, in the PubMed database, using the Medical subject headings (MeSH) terms related to herpes simplex virus or herpes zoster (namely, shingles)combined with COVID-19. Accordingly, the reports of the concomitant herpes infection andCOVID-19, receiving concurrent antiviral drugs for herpetic lesions were included. Results: Out of 90 articles, 11 records reporting the cases of herpes infection and concurrent laboratory-confirmed COVID-19, receiving antiherpetic therapies, were reviewed. There were28 patients (age range of 7-82 years) with laboratory-confirmed COVID-19, concomitant with reactivation of herpes infection, receiving antiviral drugs alongside candidate COVID-19treatment regimens, but no mortality. The mean (standard deviation [range]) age of these 28patients during treatment was 56.4 (18.6 [7-82]) years, and the majority were male (n=18, 64.3%). A total number of 20 patients had also received ACV and eight cases had been administered with other two antiviral compounds, including seven cases with valacyclovir, and one case with famciclovir, with no mortality. Conclusion: The potential use of ACV, as an add-on therapy, along with candidate COVID-19treatment regimens was proposed in this study. However, further clinical trials are recommended to test this hypothetical adjuvant therapy.